MiR‐34c Enhances Mouse Spermatogonial Stem Cells Differentiation by Targeting Nanos2. Issue 2 (February 2014) - Yu, Meng; Mu, Hailong; Niu, Zhiwei; Chu, Zhili; Zhu, Haijing; Hua, Jinlian
ABSTRACT miRNAs are expressed in many mammalian cells, acting specific roles in regulating gene expression or mediating special mRNAs cleavage by targeting their 3′‐untranslated region (3′UTR). Some miRNAs are essential and important for animal development. However, it is still unclear what the relationship is between miR‐34c and mammalian spermatogonial stem cells (SSCs). We found that a conserved microRNA‐34c through its target‐Nanos2, regulating SSCs' differentiation in mouse. Immunohistochemistry analysis of Nanos2 and miR‐34c FISH results revealed the opposite expression trends between them. Seven bioinformatics websites and programs predicted that miR‐34c has interaction sites in Nanos2's 3′UTR. Dual‐luciferase reporter vector and mutated dual‐luciferase reporter vector analysis validated that they are interacted. After transfection miR‐34c mimics into mouse SSCs, or miR‐34c lentiviral vector in vitro co‐cultivation with seminiferous tubules, and Western blot analysis demonstrated that miR‐34c over‐expression could suppress Nanos2 expression in post‐transcription level. Our experiments identified that miR‐34c may promote meiosis process by interacting with Nanos2 leading up‐regulation of Stra8 in mouse spermatogonial stem cells. J. Cell. Biochem. 115: 232–242, 2014. © 2013 Wiley Periodicals, Inc.